OPTIMALISASI KINERJA BENGKEL PUSAT PERALATAN DALAM PEMELIHARAAN ALAT UTAMA SISTEM SENJATA MATRA DARAT (STUDI DI BENGPUSPAL, BANDUNG) - , Rulady Soedjono Dorestia, Dr. Armaidy Armawi, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to: (1) assess the performance Central Workshop Weaponry (Bengpuspal) located in Bandung, which must be optimized for the existence of Bengpuspal will increase, (2) examine what obstacles faced in efforts to optimize, and (3) reviewed the efforts taken to optimize the performance of Central Workshop Weaponry This study used qualitative methods, in which more data analysis technique is conducted simultaneously with data collection as researcher in the field with a grand tour and miniature question, analyze its data with domain analysis. Studies of Central Workshop Weaponry located in Bandung, where data collection is done through observation, interview and literature study. The results showed that: the performance of Central Workshop Weaponry personnel in carrying out the main task has not run well, which is seen from the aspect of human resources, infrastructure, and funding / budged that are objects of maintenance and repair of the main tool of weapon system (alut sista). There are some problems in performance-solving solutions should be found through the optimization of performance with measures such as: coordination, education, and work programs of the main tool of weapon system maintenance. Then performed with the implementation of human resource aspects of compliance strategy skills or improving the quality of human resources through: empowering leadership, strengthening of institutional structures, and education / training. Application of infra-structural aspects of the strategy through: the development of infrastructure, procurement of machinery to replace old machines and software as a supporter. As an implementation of the strategy aspect of funding / budged in supporting performance optimization Central Workshop Weaponry by: the empowerment of budgeting, policy solutions. Optimizing the performance has to be cultivated, so that the existence Central Workshop Weaponry increases and the main tool of weapon system of ground to increase its readiness.